Hubungan Faktor Sosial Ekonomi dan Ketahanan Pangan terhadap Kejadian Stunting pada Balita - Wardani, Dyah Wulan Sumekar Rengganis; Wulandari, Marita; Suharmanto, Suharmanto (Jurnal Kesehatan, 2020)
Indonesia ranks third as a country with the highest stunting prevalence in Southeast Asia in 2017. Bandar Lampung, is one of the cities with a high prevalence of stunting; and Teluk Betung Selatan Subdistrict is an area with the highest prevalence of stunting in Bandar Lampung. This study aims to analyze the relationship between socioeconomic factors and food security on the incidence of stunting in children under five years. This study is a case-control study, with a case sample of 50 families who have stunted children under five years and the control sample is 50 families who have normal children under five years. The research variables included socioeconomic factors (education and income), food security factors (family food insecurity and food diversity), and the incidence of stunting, which were then analyzed by Chi-Square. The results showed that there was a relationship between socioeconomic factors and family food insecurity to the incidence of stunting. Therefore, stunting control programs need to involve these two factors in the intervention to reduce stunting in children under five years.